Can dynamic ultrasonography replace urodynamics in the follow‐up of patients with myelomeningocele? A prospective concurrent study. Issue 1 (23rd October 2018) - Bortolini, Tiago; Lucena, Iara Regina Siqueira; da Silva Batezini, Nelson Sivonei; Rosito, Tiago Elias; Araújo, Thiago; Carneiro, Bruna Brasil; Tavares, Patric Machado; Souza, Pablo Cambeses; Neto, Brasil Silva
Abstract : Aims: To evaluate the accuracy of dynamic ultrasonography (DUS), as a feasible alternative diagnostic method to identify detrusor overactivity (DO) in patients with neurogenic bladder. Methods: We performed concurrent analysis of 81 pairs of urodynamic study (UDS) and DUS, in 63 patients with myelomeningocele (MMC), from June 2014 to February 2017. The assessment focused on bladder behavior during the filling phase, DO evaluation, DO with leakage, compliance, and maximum cystometric capacity (MCC). Results: Patient age ranged from 3 months to 34 years (median, 84 months); 47.6% were male. Overall, 9.5% of patients had chronic kidney disease, 20.6% had recurrent urinary tract infection, 19.05% had vesicoureteral reflux, and 69.8% had constipation. Anticholinergic therapy was used by 41.3% of patients. DO was observed in 45.67% of patients and DO with leakage in 42.6%. Mean bladder compliance was 10.39 mL/cmH2 O and normal MCC was 56.79%. DUS had 91.89% sensitivity in identifying DO, 88.64% specificity, 87.18% positive predictive value, 92.86% negative predictive value, and 90.12% accuracy, with a kappa coefficient of 0.8 ( P < 0.001). Conclusion: MMC follow‐up is essential because urinary parameters can change during patient growth. The standard examination is invasive and has related complications, making noninvasive evaluation a desirable alternative, like DUS. Our data suggest that DO and MCC can be evaluated using DUS in patients with MMC. UDS should be performed in patients with abnormal findings on ultrasound evaluation or those with worsening of urinary tract function.